Herbivorous Caterpillars Can Utilize Three Mechanisms to Alter Green Leaf Volatile Emission. Issue 2 (19th January 2019) - Jones, Anne C; Seidl-Adams, Irmgard; Engelberth, Jurgen; Hunter, Charles T; Alborn, Hans; Tumlinson, James H
Abstract: Green plants emit green leaf volatiles (GLVs) as a general damage response. These compounds act as signals for the emitter plant, neighboring plants, and even for insects in the ecosystem. However, when oral secretions from certain caterpillars are applied to wounded leaves, GLV emissions are significantly decreased or modified. We examined four caterpillar species representing two lepidopteran families for their capacity to decrease GLV emissions from Zea mays leaf tissue. We also investigated the source of the GLV modifying components in the alimentary tract of the various caterpillars. In Spodoptera exigua (Hübner) (Lepidoptera: Noctuidae), Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae), Trichoplusia ni (Hübner) (Lepidoptera: Noctuidae), and Manduca sexta (Linnaeus) (Lepidoptera: Sphingidae), we found three distinct mechanisms to modify GLV emission: a heat-stable compound in the gut, a heat-labile enzyme in salivary gland homogenate (previously described in Bombyx mori (Linnaeus) (Lepidoptera: Bombycidae), and an isomerase in the salivary gland homogenate, which catalyzes the conversion of ( Z )-3-hexenal to ( E )-2-hexenal (previously described in M. sexta ). These mechanisms employed by caterpillars to suppress or modify GLV emission suggest a counteraction against the induced indirect volatile defenses of a plant and provides further insights into the ecological functions of GLVs.